The Connection between Galaxy Mergers, Star Formation, and Active Galactic Nuclei Activity in the HSC-SSP - Kiyoaki Christopher Omori; Connor Bottrell; Sabine Bellstedt; Aaron S. G. Robotham; Hassen M. Yesuf; Andy D. Goulding; Marcin Sawicki; Tohru Nagao; Tsutomu T. Takeuchi (The Astrophysical Journal)
Internal gas inflows driven by galaxy mergers are considered to enhance star formation rates (SFRs), fuel supermassive black hole growth, and stimulate active galactic nuclei (AGNs). However, quantifying these phenomena remains a challenge, due to difficulties both in classifying mergers and in quantifying galaxy and AGN properties. We quantitatively examine the merger–SFR–AGN connection using Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP) galaxies using novel methods for both galaxy classification and property measurements. Mergers in HSC-SSP observational images are identified through fine-tuning Zoobot, a pretrained deep representation learning model, using images and labels based on the Galaxy Cruise project. We use galaxy and AGN properties that were produced by fitting Galaxy and Mass Assembly spectra using the spectral energy distribution fitting code P ro S pect , which fits panchromatically across the far-ultraviolet through far-infrared wavelengths and obtains galaxy and AGN properties simultaneously. Small differences are seen in SFR and AGN activity between mergers and controls, with ΔSFR = −0.009 ± 0.003 dex, Δ f _AGN  = −0.010 ± 0.033 dex, and Δ L _AGN  = 0.002 ± 0.025 dex. After further visual purification of the merger sample, we find ΔSFR = −0.033 ± 0.014 dex, Δ f _AGN  = −0.024 ± 0.170 dex, and Δ L _AGN  = 0.019 ± 0.129 dex for pairs, and ΔSFR = −0.057 ± 0.024 dex, Δ f _AGN  = 0.286 ± 0.270 dex, and Δ L _AGN  = 0.329 ± 0.195 dex for postmergers. These numbers suggest secular processes being an important driver for star formation and AGN activity, and present a cautionary tale when using longer-timescale tracers.